Wayang Gajah Mada In Visual And Performing Arts: Research-Based Innovation of Javanese Puppetry and its Reception in the Academic and Artistic Environments - Rudy Wiratama; Sindung Tjahyadi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
Wayang Gajah Mada (WGM), named after its main character and also the initiator university, was one of a few Javanese puppetry which used historical chronicles as its repertoire.This genre of wayang was designed from 2017 and has been performed several times both inside and outside the Universitas Gadjah Mada with various formats, from pakeliran multimedia to a conventional pakeliran semalam (all-night performance). Aside of its particular repertoires that depicted the biography of Mahapatih Gajah Mada, the team of Universitas Gadjah Mada also designed a special figures for the performances, which formed a new kind of puppet genre. The challenge began when it came publicly through many occasions, such as FGDs, national seminar, and the performances themselves. As a new puppet genre, both in visual and performance terms, the WGM have to proof its relevancy and significance to both of the academic and artistic societies, so it could guarantee its own sustainability for a long time. This article aims to answer: (a) what is the main concept of WGM both in visual and performative context, and also (b) how was the reception of both academic and artistic environments concerning the creation of this new puppet. Using the interview and observation methods, this article finds that WGM having a “Nusantara” concept both in visual and performative ways, and it received a good receptions from both academic and artistic environment which used the puppets in their performances. But despite of these positive reviews, it needs to struggle for its continuity in the future.